The human planet : how we created the Anthropocene - Lewis, Simon L.; Maslin, Mark (Yale University Press, 2018)
A remarkable exploration of the science, history, and politics of the Anthropocene, one of the most important scientific ideas of our time, from two world-renowned expertsMeteorites, mega-volcanoes, and plate tectonics--the old forces of nature--have transformed Earth for millions of years. They are now joined by a new geological force--humans. Our actions have driven Earth into a new geological epoch, the Anthropocene. For the first time in our home planet's 4.5-billion-year history a single species is increasingly dictating Earth's future.To some the Anthropocene symbolizes a future of superlative control of our environment. To others it is the height of hubris, the illusion of our mastery over nature. Whatever your view, just below the surface of this odd-sounding scientific word, the Anthropocene, is a heady mix of science, philosophy, and politics linked to our deepest fears and utopian visions.Tracing our environmental impacts through time, scientists Simon Lewis and Mark Maslin reveal a new view of human history and a new outlook for the future of humanity in the unstable world we have created.